Why did Ukrainian Red Army Men Go Over to the Germans? The Case of Defectors to the Wehrmacht’s 296 Infantry Division, 1942–1943 - Edele, M. (Український історичний журнал, 2019)
The purpose of this study is to analyse the reasons for defection among
Ukrainian Red Army men during World War II. The research methodology is
a combination of quantitative and qualitative methods. We analyse interrogation
reports of Red Army defectors created by the counter-intelligence officer of the German
296 ID both for the reasons defectors gave for crossing the frontline and for the
frequency their reasons fell into certain categories. We compare these data with the
larger group of Soviet defectors, including other Soviet nationalities. The scientific
novelty consists in combining cultural history with quantification and extending a
methodology developed for Red Army defectors as a whole to the subset of Ukrainians
among them. The article’s source base is multi-archival, drawing on Ukrainian and
Russian archives in addition to the German military archive. Conclusions. In the
aggregate Ukrainians were not motivated in significantly different ways from Soviet
defectors of other nationalities. Ukrainians were more often politicized than other
nationalities, but the broad social and political grievances they expressed were shared
by many Soviet citizens. Many of the Ukrainian defectors who were politicized enough
to want to fight against the Soviets to liberate their “homeland” were imagining this
home as the multi-national Soviet Union rather than a Ukrainian national territory.
The political grievances which motivated these politicized Ukrainians were political
(lack of freedom, repression) or social (the collective farms, terrible living conditions)
rather than national (freedom for Ukraine). Ukrainian nationalists were in the
minority among defectors, and tended to come from the formerly Polish territories
annexed after the start of World War II in Europe. Метою цього дослідження став аналіз причин перебіжництва
серед червоноармійців-українців під час Другої світової війни. Методологія
становить собою поєднання кількісного та якісного методів. Предметом аналізу
виступають написані офіцером контррозвідки 296-ї піхотної дивізії вермахту
протоколи допитів перебіжчиків-червоноармійців – як з огляду на характер
причин, котрі спонукали їх перетнути лінію фронту, так і на частоту мотивів
різних категорій. Ці дані порівнюються з показниками більшої групи радянських
перебіжчиків різних національностей. Наукова новизна полягає в поєднанні
культурної історії з квантитативним підходом і застосуванням методології,
розробленої для вивчення проблеми перебіжчиків-червоноармійців у цілому та
підгрупи українців зокрема. Джерельна база статті складається з українських
та російських архівних матеріалів, які доповнюють дані німецького військового
архіву. Висновки. У цілому мотивація українців не надто відрізнялася від тієї,
яку мали радянські перебіжчиків інших національностей. Хоча українці часто
були більш політизованими, але назагал соціальні й політичні нарікання, що їх
вони висловлювали, поділяли багато радянських громадян. Чимало українських
перебіжчиків, які були достатньо політизованими для бажання боротися
проти «совєтів», за звільнення «Батьківщини», уявляли під останньою радше
багатонаціональний СРСР, аніж суто українську національну територію.
Мотиви політизованих українців були власне політичними (відсутність
свободи, репресії) або соціальними (колгоспи, жахливі умови життя), а не
національними (свобода для України). Українські націоналісти становили
меншість серед перебіжчиків і найчастіше походили з колишніх польських
територій, анексованих на початку Другої світової війни в Європі.